Physical activity and physiological profiles of elite international female field hockey players across the quarters of competitive match play - McGuinness, A.; Malone, S.; Hughes, B.; Collins, K. (The Journal of Strength and Conditioning Research, 2019)
The aim of the current investigation was to quantify the physical and physiological demands of elite international female field hockey across the quarters of match-play. Twenty-seven elite international female field hockey outfield players (23 ± 3 years; 162.6 ± 13.0 cm; 66.0 ± 6.0 kg) participated in the current observational study during the 2016-2017 season. Participants were monitored using global positioning system technology and HR monitors. Players were categorized based on 3 different playing positions. Activity was categorized into total distance (in meters), relative total distance (m/min), low-, moderate-, and high-intensity distance (m), maximum velocity (km/h), and percentage maximal velocity (%). Physiological demands were quantified through players peak heart rate (HRPeak), which was classified based on the player's individual HRmax determined using a Yo-Yo intermittent recovery level 1 test. Players spent on average 38 ± 8 minutes in match play. The total distance covered was 4,847 ± 583 m (127.6 ± 15.6 m/min). Defenders covered a greater total distance across all 3 positions (p = = 0.05). The midfielders covered a greater moderate-intensity distance (p = 0.001), whereas the forwards covered more high-intensity distance (p = 0.001). The HRpeak of the players was 198 ± 4 b/min with a mean exercise intensity of 95 ± 1% HRmax. The time spent >70% HRmax decreased significantly across the quarters (p = 0.01, n2 = 0.03). Defenders were found to spend more time >85% HRmax when compared with other positions (p = 0.001, n2 = 0.28). The current study provides normative data that coaches should consider when developing training drills to better optimize the positional physical and physiological activity profiles that best replicate match play.